Analysis of human reliability in accidents and incidents in a chemical industry - Bastos, Bruna Moura (Seven Editora, 2023)
Human Reliability has increased its space in environments where processes have a higher level of danger and among them are the chemical industries. In these industries, the periods in which maintenance interventions occur to guarantee the reliability of the equipment and operational continuity are recurrent. During interventions, the pace at which activities are carried out becomes faster, in addition to having a greater turnover of people performing the services. Therefore, this whole scenario makes the work environment more vulnerable to risks and it is the moment when risk analysis methodologies occupy a strategic place. To acquire greater support in carrying out the activities, maintenance procedures are elaborated, however, studies show that these are often unknown and/or misused. In this sense, this study aims to understand the importance of using the human factor approach in ensuring safe work environments, analyzing Human Reliability through the PUMA methodology, and associating with concepts such as psychological safety, the role of leadership and Communication. In addition, the study analyzes the root cause of some accidents and incidents that have occurred, using some methodologies such as the Cause Tree and associating them with concepts considered important for Human Reliability. DOI: https://doi.org/10.56238/devopinterscie-002